Comparison of Antibacterial Activity Tests of 70% and 96% Ethanol Extract on Siam Sambas Orange Leaves (Citrus nobilis var. microcarpa) - Zakiah, Mistika; Asseggaf, Syarifah Nurul Yanti Rizki Syahab; Ulfah, Ridha; Putri, Triyana Harlia; Hendrayana, Bimo; Putra, Galih Abisatya Hartono (Faculty of Medicine, Universitas Tadulako, 2025)
Background: Antibiotic resistance against bacterial infections such as Escherichia coli and Staphylococcus aureus, prevalent in tropical regions, necessitates alternative treatments. One potential solution is utilizing secondary metabolites found in Sambas Siamese orange leaves. These compounds may serve as antibacterial agents. Objective: This study aims to compare the effectiveness of 70% and 96% ethanol as solvents for extracting secondary metabolites from Sambas Siamese orange leaves. Methods: Extraction was performed using two types of solvents (70% and 96% ethanol) to obtain secondary metabolites. Antibacterial activity was tested using the disc diffusion method (Kirby-Bauer), and data were analyzed with One-Way Analysis of Variance (ANOVA). Results: Extraction with 96% ethanol yielded flavonoids (+++), terpenoids (++), steroids (++), and phenols (++). Meanwhile, extraction with 70% ethanol produced Mayer alkaloids (++), flavonoids (++), saponins (+), steroids (+++), and phenols (+++). The 96% ethanol solvent was more effective in extracting limonene compounds from the leaves. Conclusion: The 96% ethanol solvent demonstrated higher effectiveness compared to 70% ethanol in extracting secondary metabolites, particularly limonene, which has potential antibacterial properties, from Sambas Siamese orange leaves